Mental well-being and religious values among Muslims across four cities - Ismail, Nik Ahmad Hisham; Tekke, Mustafa; Fatah, Ismail; Rafeeq, Shazmin (IIUM Press, 2022)
Mental well-being as a subject is much integrated with other fields of knowledge. Thus, in this study, chosen variables common to other constructs in different fields of knowledge such as self-development, self-acceptance, personal goal, resilience, piety, hope and social interest were used as significant constructs to correlate positively with mental well-being. The WarwickEdinburgh Mental Well-Being Scale (W-EMWS) was mainly used to gauge mental well-being among respondents in this study. The focus of the study was to investigate the mental well-being among the diverse Muslim groups in selected cities in different countries with differences in nationalities, cultures, and values. The study was to determine whether religiosity values among the different Muslim groups contributed to their mental well-being. A sample size of 989 respondents was selected from Istanbul, Republic of Türkiye; Kuala Lumpur, Malaysia; Lagos, Nigeria; and London, United Kingdom. The results from this study indicated that several factors such as self-acceptance, social interest, and self-development significantly correlated to mental well-being among Muslim respondents. As predicted, the study shows varying degrees of correlation among the Muslim groups selected in different cities. However, religious values, such as piety and hope were moderately correlated with mental well-being among the Muslim groups. The findings show promising results and future studies should expand into investigating the exploratory modelling of mental well-being and differences in the potential means of religious values across other Muslim countries from different backgrounds.